58.3k views
1 vote
I can not figure out how to start this problem

I can not figure out how to start this problem-example-1
User Alryosha
by
5.2k points

1 Answer

3 votes

At first, we have to find y', then find y'(2)

The given equation is


3x^2+4x+xy=2

We want to use the rule of the product in differentiation


uv=u^(\prime)v+uv^(\prime)

Then to differentiate xy, it will be


\begin{gathered} u=x,v=y \\ xy\rightarrow(1)x^(1-1)(y)+x(1)y^(1-1)y^(\prime) \\ xy\rightarrow x^0y+xy^0y^(\prime) \\ xy\rightarrow(1)y+x(1)y^(\prime) \\ xy\rightarrow y+xy^(\prime) \end{gathered}

We will differentiate it with respect to x


3(2)x^(2-1)+4(1)x^(1-1)+(1)x^(1-1)(y)+x(1)y^(1-1)y^(\prime)=0

Simplify each term


\begin{gathered} 6x^1+4x^0+x^0y+xy^0y^(\prime)=0 \\ 6x+4(1)+(1)y+x(1)y^(\prime)=0 \\ 6x+4+y+xy^(\prime)=0 \end{gathered}

Now, we need to separate y' on the side and the other terms on the other side


xy^(\prime)=-6x-y-4

Divide them by x


\begin{gathered} (xy^(\prime))/(x)=(-6x-y-4)/(x) \\ y^(\prime)=(-6x-y-4)/(x) \end{gathered}

We need to find y'(2) by substitute x by 2 and y by -9


\begin{gathered} y^(\prime)(2)=(-6(2)-(-9)-4)/(2) \\ y^(\prime)(2)=(-12+9-4)/(2) \\ y^(\prime)(2)=(-7)/(2) \end{gathered}

The answer is -7/2

User Mohamed Salah
by
5.0k points